Prospective History Teachers Worldviews on Sensitive and Controversial Issues in History Classes - Fitrianto, Robby Fajar; Kurniawan, Ganda Febri (Indonesian Journal of History Education, 2023)
This study aims to analyze the teacher's world view of sensitive and controversial issues in history learning. This research was carried out using qualitative methods with a descriptive approach. This study involved 90 participants. Data collection in this study used interview techniques relying on two techniques: first, one-on-one interviews with informants and second, group interviews or clustered discussions. Analysis of the research data using an interactive model. The results of this study indicate that the concept of sensitive and controversial issues in history learning has an important position for developing the thinking skills of prospective history teachers. To be able to manage sensitive and controversial issues requires an understanding of innovative learning strategies and evaluations. This study concludes that sensitive and controversial issues in history learning need to be mastered by history teacher candidates who are currently studying, so that this knowledge can have implications for history lessons that train critical thinking skills in schools.